2000
DOI: 10.1002/1096-8628(20000717)93:2<122::aid-ajmg8>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Absence of association between a common mutation in the methylenetetrahydrofolate reductase gene and preeclampsia in Japanese women

Abstract: An association between preeclampsia (PE) and a common missense mutation of the methylenetetrahydrofolate reductase gene (MTHFR), a C to T substitution at nucleotide 677 (C677T), which converts an alanine to a valine residue, has been reported in Italian and Japanese populations. We examined 101 cases of hypertension in pregnancy (HP), including 73 cases of PE, and 215 normal pregnancy controls to confirm the association in Japanese women. No significant differences of the frequency of the T677 allele frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 24 publications
(30 reference statements)
0
20
1
Order By: Relevance
“…The main characteristics of the included studies are presented in Table S1. Among all studies, 42 studies were performed among East Asians [27], [28], [33], [37], [42], [43], [48], [50], [54], [56], [57], [60], [65], [73], [75], [78], [79], [81], [86]–[90], [94]–[97], [102], [103], [105]–[107], [115]–[118], [122], [124], [131], [132], [134], [136], 54 among Caucasians [29], [31], [32], [34], [35], [38][41], [44][47], [49], [51][53], [55], [59], [63], [64], [66], [67], [69]–[72], [74], [76], [77], [80], [82], [84], [92], [93], [98][101], …”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the included studies are presented in Table S1. Among all studies, 42 studies were performed among East Asians [27], [28], [33], [37], [42], [43], [48], [50], [54], [56], [57], [60], [65], [73], [75], [78], [79], [81], [86]–[90], [94]–[97], [102], [103], [105]–[107], [115]–[118], [122], [124], [131], [132], [134], [136], 54 among Caucasians [29], [31], [32], [34], [35], [38][41], [44][47], [49], [51][53], [55], [59], [63], [64], [66], [67], [69]–[72], [74], [76], [77], [80], [82], [84], [92], [93], [98][101], …”
Section: Resultsmentioning
confidence: 99%
“…The frequency of T-carriers genotypes was found significantly higher among the women with PE than the control groups indicated that MTHFR C677T polymorphism would be expected to play a major role to bring about PE. Some studies reported significantly increased prevalence of MTHFR C677T among cases [22][23][24]49]. In contrast, other 1 9 9 7 J a p a n A s i a n Three meta-analysis summarizing studies on association between the MTHFR C677T polymorphism and the risk of PE until August 2012 have been performed [51][52][53], however, their meta-analysis did not perform analyses on association between the MTHFR A1298C and the risk of PE.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, the meta-analysis by Xia et al (95) reported that the TT genotype compared with the CC and CT genotypes carried a significantly greater risk of preeclampsia (by 76%) among Asian women only, whereas in Caucasian women this increased risk was not evident. It is worth noting however that a much greater number of large-scale studies in this area have been conducted within Asian populations with far fewer studies conducted in Caucasian populations; a factor that limits Sohda et al (87) 425 Japan 2·5 (1·3, 4·8) Grandone et al (88) 225 Italy 1·8 (1·0, 3·5) Kupferminc (96) 144 Israel 2·9 (1·0, 8·5) Powers et al (97) 237 Caucasian women 1·28 (0·58, 2·79) Kobashi et al (98) 316 Japan 0·68 (0·30, 1·55) Laivuori et al (99) 216 Finland 0·50 (0·14, 1·77) Rigo et al (100) 221 Caucasian women 1·13 (0·38, 3·37) Morrison et al (101) 404 Scotland 1·00 (0·55, 1·82) Prasmusinto et al (102) 112 Germany and Croatia 0·28 (0·03, 2·47) Pegoraro et al (103) 609 South African (Black) 0·62 (0·06, 6·90) Perez-Mutul et al (91) 325 Mexico 0·94 (0·59, 1·49) Williams et al (104) 304 Peru 1·6 (0·7, 3·8) Yilmaz et al (105) 111 Turkey 0·84 (0·26, 2·67) Also-Rallo et al (79) 165 Spain 0·73 (0·31, 1·76) Hernandez-Diaz et al (86) 154 USA/Canada 3·0 (1·2, 7·7) Stiefel et al (106) 584 Spain 0·92 (0·50, 1·71) the extent to which different populations can be compared. An additional limitation is that genotype-driven recruitment is generally not undertaken in these studies, a feature that is reflected by the relatively small numbers of pregnant women with the TT genotype being investigated and these raised the concern that many such studies may be statistically underpowered.…”
Section: Role Of the Mthfr Genotype In Determining The Risk Of Hypertmentioning
confidence: 99%